Workplace Stress, Social Support and Coping Strategy as Predictors of Mental Well-Being among Nurses in Ibadan - Emmanuel Uye; Layade Adejuwon; Esohe Ehondor (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
This study examines workplace stress, social support and coping strategy as predictors of mental well-being among nurses in Ibadan North Local Government (LGA) Oyo State, Nigeria. Cross-sectional survey research design was adopted while purposive sampling technique was used to select the LGA. Data were collected using validated scales from 163 participants and analyzed using zero-order correlation statistics and multiple regression analysis to test four hypotheses which were accepted at p < .05 level of significance. The result revealed that significant others support and friends social support independently predicted mental well-being among nurses among study participants. Furthermore, coping strategy and workplace stress independently predicted mental well-being among nurses in the study population. Finally, workload stress, social support and coping strategy jointly predicted mental well-being among study participants. The study concluded that workplace stress, social support and coping strategy are robust predictors of mental well-being among nurses. It is recommended that management of health institutions should integrate training and education programmers that focus on coping strategy and stress reduction techniques that foster positive relationships with friends and significant others to enhance mental well-being among nurse’s workforce.